2012
DOI: 10.1016/j.quascirev.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Timing and depositional environments of a Middle Pleistocene glaciation of northeast England: New evidence from Warren House Gill, County Durham

Abstract: At various times during the Quaternary, north-eastern England was a zone of confluence between dynamic ice lobes sourced from the Pennines, northern Scotland, the Cheviots, and Scandinavia. The region thus has some of the most complex exposures of Middle to Late Pleistocene sediments in Britain, with both interglacial and glacial sediments deposited in terrestrial and marine settings. We investigated sedimentary sequences exposed on the coastline of County Durham at Warren House Gill, and present a new model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 112 publications
1
31
0
Order By: Relevance
“…Specifically, heavy mineral assemblages diagnostic of the Grampian Highlands and the north-east coast of Scotland, together with Late Jurassic palynomorphs sourced from the Moray Firth Basin or from northern England, have been identified in the Swarte Bank, Fisher and Bolders Bank formations of MIS 12, 6 and 2 respectively. A broadly similar suite has also been identified in the Horden Till of the Durham coast and the Skipsea Till of eastern Yorkshire, which were deposited by the North Sea Ice Lobe of the last BIIS during the Dimlington Stadial (Davies et al, 2009(Davies et al, , 2012. It has been difficult to reconcile this recurring south-eastward trajectory from the Moray Firth with ice sheet reconstructions placing low ice divides stretching across the central North Sea Basin between Scotland and Norway (Davies et al, 2011, fig.11; Busfield et al, 2015, fig.7).…”
Section: Evidence For Stages During the Local Lgmmentioning
confidence: 83%
“…Specifically, heavy mineral assemblages diagnostic of the Grampian Highlands and the north-east coast of Scotland, together with Late Jurassic palynomorphs sourced from the Moray Firth Basin or from northern England, have been identified in the Swarte Bank, Fisher and Bolders Bank formations of MIS 12, 6 and 2 respectively. A broadly similar suite has also been identified in the Horden Till of the Durham coast and the Skipsea Till of eastern Yorkshire, which were deposited by the North Sea Ice Lobe of the last BIIS during the Dimlington Stadial (Davies et al, 2009(Davies et al, , 2012. It has been difficult to reconcile this recurring south-eastward trajectory from the Moray Firth with ice sheet reconstructions placing low ice divides stretching across the central North Sea Basin between Scotland and Norway (Davies et al, 2011, fig.11; Busfield et al, 2015, fig.7).…”
Section: Evidence For Stages During the Local Lgmmentioning
confidence: 83%
“…Critically, the glaciogenic deposits upon which the Wolstonian Glaciation was identified were shown in Perrin et al (1979) to be part of the same association of deposits as those considered to be of Anglian age further east, and the associated Wolstonian fluviatile deposits that underlie the glaciogenic sediment have been shown to be pre-Anglian in age (Rose, 1987(Rose, , 1994 rather than younger than Anglian as proposed by Shotton (1976Shotton ( , 1983. Traces of other late Middle Pleistocene glaciations were still identified at specific localities in east Lincolnshire, Yorkshire and Durham (Catt and Penny, 1966;Davies et al, 2012), and reference to these sites and their significance can be found in Bowen et al (1986) which also allocates the glaciations to geochronometric ages and Marine Isotope Stages. Thus the most extensive glaciation of Britain was considered to have occurred during MIS 12, and subsequent late Middle Pleistocene glaciations are interpreted as occurring during MIS 8 (in south Wales) in the west Midlands and eastern England, reaching positions just beyond the limit of the Last Glaciation (Bowen et al, 1986) ( Figure 4B).…”
mentioning
confidence: 88%
“…As a result of a detailed OSL dating programme reported in this paper, and existing radiocarbon dates (Ó Cofaigh and Evans, 2007), it is demonstrated that the palaeoshoreline formed during MIS 4-3 with a level determined by glacio-isostatic deformation, and that the glacial deposits previously considered to have formed prior to the Last Glaciation were formed by a rapid and short lived advance (surge) around 24 ka BP. Ireland was therefore almost completely submerged beneath the ice sheet of the Last (MIS 2) Glaciation.The issue of pre-MIS 2 glaciations is examined in the paper by Davies et al (2012) which provides a detailed examination of the earlier part of the stratigraphic sequence at a long-studied site in northeast England. The site in question (Warren House Gill in County Durham) has been known for pre-LGM till and raised beach deposits and has been interpreted as evidence for Scandinavian-sourced glaciation of eastern England in MIS 6.…”
mentioning
confidence: 99%
See 2 more Smart Citations